Identification of stress factors in returning migrants in Latvia - Ozola-Cīrule, Iveta; Martinsone, Baiba (Frontiers in Psychology, 2025)
This study investigates the psychological stress factors faced by return migrants before, during, and after their return to Latvia. Employing a Grounded Theory methodology, we conducted in-depth interviews with 21 return migrants and identified five key themes: pre-return context, identity, perceived social support, psychological wellbeing, and factors that help or hinder re-adjustment. Notably, psychological stress prior to return often exceeds post-return stress, highlighting the critical yet understudied pre-return phase. Key contributors to return migration stress include unmet expectations, feelings of alienation, identity struggles, and inadequate institutional support. By highlighting these stress factors, this research not only enhances the understanding of return migration from a psychological standpoint but also lays the foundational groundwork for the development of a comprehensive theoretical framework that encompasses a broader spectrum of factors influencing return migration stress. The study advocates for a holistic approach to supporting return migrants, emphasizing the integration of psychological resources with practical assistance to foster successful reintegration into their home country.